Distributed embedded control systems design with verification support - I. V. Shoshmina (Моделирование и анализ информационных систем, 2010)
We consider a problem of integrating a formal method of verification (model checking) into the process of designing complex distributed software systems to improve the quality of software. We use an approach based on the Model-Driven Engineering. It allows us to structure the design process by selecting and verifying a system core, consisting of independent subsystems and being responsible for logical management of the entire system as a whole. The proposed method was tested on a real control system of vessel power supply.